KEPRIBADIAN YANG BAIK UNTUK KEEFEKTIFAN KEPEMIMPINAN KEPALA SEKOLAH - Vonny Angeli Sudharta; Ibrahim Bafadal; Sultoni Sultoni (Universitas Negeri Malang, 2018)
Abstract: Personality is inherent in individuals who can then be influenced by the environment, in which personality leadership has various elements. In this study the aim is to find out (1) the character possessed by the principal, (2) the integrity of the principal's personality, (3) the desire of the principal in self-development, (4) openness to the implementation of duties and functions in carrying out the leadership of the principal, (5) Self-control of the principal in overcoming problems in SMPN 11 and SMPN 18 Malang. Where this is in order to determine the effectiveness of the principal's leadership. The method used in this study is qualitative descriptive using multi-site design. Data collection techniques used are interviews, observation and documentation. The subject of this study was the Head of SMPN 11 and SMPN 18 Malang, with the source of the principal, vice principal, administration, teachers and students. Data analysis is done by reducing, presenting data, drawing conclusions and verification. The results of this study are, (1) The principal has good behavior in accordance with the indicators of the principal's personality competency. (2) The Head of SMPN 11 and 18 Malang has good personality integrity which is shown by the attitude of honesty, fairness, discipline, etc. (3) In achieving the goals of the principal make the program planned carefully and implemented as well as possible so that each goal is achieved. (4) The principal also shows openness in carrying out all the duties of the principal, both opinions and concerns for all school members. (5) The principal has good self-control in problem solving. Keywords: personality, effectiveness of leadership, headmaster Abstrak: Kepribadian merupakan sifat yang melekat pada individu yang kemudian dapat dipengaruhi oleh lingkungan, dimana dalam kepemimpinan kepribadian memiliki berbagai unsur. Dalam penelitian ini memiliki tujuan untuk mengetahui (1) Akhlak yang dimiliki kepala sekolah, (2) Integritas kepribadian kepala sekolah, (3) Keinginan kepala sekolah dalam pengembangan diri, (4) Keterbukaan terhadap pelaksanaan tugas dan fungsi dalam pelaksanaan kepemimpinan kepala sekolah, (5) Pengendalian diri kepala sekolah dalam mengatasi permasalahan di SMPN 11 dan SMPN 18 Malang. Dimana hal tersebut guna mengetahui keefektifan kepemimpinan kepala sekolah. Metode yang digunakan peneliti dalam penelitian ini yaitu kualitatif deskriptif dengan menggunakan rancangan multi situs. Teknik pengumpulan data yang digunakan yaitu wawancara, observasi dan dokumentasi. Subjek penelitian ini adalah Kepala SMPN 11 dan SMPN 18 Malang, dengan sumber kepala sekolah, wakil kepala sekolah, tata usaha, guru dan siswa. Analisa data dilakukan dengan cara reduksi, penyajian data, penarikan simpulan dan verifikasi. Hasil dari penelitian ini yaitu, (1) Kepala sekolah memiliki perilaku yang baik sesuai dengan indikator kompetensi kepribadian kepala sekolah. (2) Kepala SMPN 11 dan 18 Malang memiliki integritas kepribadian baik yang ditunjukkan dengan sikap kejujuran, keadilan, disiplin, dll. (3) Dalam pencapaian tujuan kepala sekolah membuat program yang sudah direncanakan matang-matang dan dilaksanakan sebaik-baiknya sehingga tiap tujuan tercapai. (4) Kepala sekolah juga menunjukan keterbukaan dalam melaksanakan segala tupoksi kepala sekolah, baik pendapat maupun hal kepedulian terhadap semua anggota sekolah. (5) Kepala sekolah memiliki pengendalian diri yang baik dalam pemecahan masalah. Kata Kunci: kepribadian, keefektifan kepemimpinan, kepala sekolah